A SYSTEMATIC REVIEW OF THE PRACTICE AND IMPACT OF TARANNUM IN QURANIC RECITATION - Ramli, Mohd Shahidan; Mohd Din , Khairil Fikri; Sahad , Mohd Nizam (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The art of tarannum, or melodious Qur’anic recitation, represents a unique intersection of linguistic beauty, theological depth, and educational tradition in Islam. Despite its longstanding role in enhancing Qur’anic engagement, systematic scholarly analysis of tarannum remains limited. This study aims to address this gap by conducting a systematic literature review (SLR) on the practice and impact of tarannum in Qur’anic recitation. The review applied advanced search techniques using the Scopus and Web of Science (WoS) databases, guided by the PRISMA framework. Using the keywords “tarannum” and “Quran,” a total of 5,741 records were initially retrieved. After rigorous screening, eligibility assessment, and removal of duplicates, 39 articles were selected for qualitative synthesis. The thematic analysis of the selected studies revealed three dominant themes: (1) Qur’anic Language and Linguistics, which highlights how melodic recitation influences syntactic structures, phonetic interpretation, and semantic richness; (2) Tafsir, Theology, and Islamic Thought, where tarannum is examined in relation to exegetical practices, theological constructs and spiritual symbolism and (3) Islamic Education and Contemporary Applications, which explores the pedagogical role of tarannum, its integration with digital tools, and its impact on learner engagement and well-being. The review demonstrates that tarannum is not merely a recitational technique, but a multifaceted tool that contributes to the preservation of Qur’anic tradition, the transmission of religious knowledge, and the enhancement of spiritual aesthetics. These findings affirm the need for deeper academic engagement with tarannum as a significant component of Qur’anic studies, and they offer a foundation for future research that integrates traditional practice with contemporary educational and technological contexts.